Pengaruh Induksi Aspergillus niger/brasiliensis Strain ATCC ® 16404™ Secara Sistemik dan Pencabutan Gigi Terhadap Jumlah Koloni pada Mukosa Gingiva - Yanuardi Kristandia; Fanny M Laihad; Astrid Palmasari (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2015)
Background: Prevention of gingival mucosal tissue damage caused by aspergillus niger the invasive fungal infection in the mouth is still difficult to determine its diagnosis and therapy. The cause of maxillary gingiva mucosal damage can be indicated as systemic fungal infections triggered by tooth extraction. There have been no research yet about the effect of invasive fungal aspergillus niger infections in the maxillary mucosa that has been performed tooth extraction and no tooth extraction. Purpose: To determine the effect of Aspergillus niger/brasiliensis strain ATCC ®16404 ™ induction systemically and tooth extraction action to the number of colonies on the maxillary gingiva mucosa. Materials and Methods: This study used post test only control group design. Thirty two adult male wistar rats were randomly divided into 4 groups: group K-, group P1 had tooth extraction, group P2 injected 0.3 ml by Aspergillus niger strain ATCC®16404 ™ 0.5 Mc Farland, P3 had extraction of maxillary tooth and injection 0.3 ml of the fungus aspergillus niger strain ATCC®16404 ™ 0.5 Mc Farland. Swabbing were applied on each group (day 1,3,5) in the maxillary mucosa and cultured on saboround dextrose agar (SDA) media with the spreader technique and incubated (37°C) for 48 hours Data were analyzed by Kruskal Wallis. Result: There is no significant difference in the amount of the fungus aspergillus niger in each group. Conclusion: Induction of aspergillus niger systemic wasn’t able to lead to significant conditions of the oral cavity, and therefore revocation isn’t a factor that that triggered the severity of the onset of aspergillus niger.